Taxa de Juros, Nível de Atividade e Distribuição: Um Modelo Dinâmico com Mark-up Bancário Endógeno - Meirelles, Antonio J. A.; Lima, Gilberto Tadeu (Estudos Econômicos (São Paulo), 2001)
The paper develops a post-kenesian macrodynamic model of capacity utilization and income distribution in which the supply of credit-money is endogenous. Nominal interest rate is determined by banks as a markup over the base rate, which is exogenously set by the monetary authority. Over time, banking markup falls with capacity utilization and rises with the inflation rate. Since firms produce according to demand under conditions of excess capacity, the equality between desired investment and saving is brought about by changes in capacity utilization. Regarding dynamics, it is seen how restrictive are the stability conditions of the equilibrium solution of the system having the real wage and the nominal interest rate as state variables.